Pengujian Kualitas Biodiesel dari Minyak Kelapa Sawit Dengan Katalis Heterogen Abu Daun Kucai (Allium schoenoprasum): Parameter Berat Katalis, Rasio Mol Minyak Terhadap Metanol dan Waktu Reaksi - Bani, Okta; David; Febianto, Toby (Jurnal Teknik Kimia USU, 2022)
The Chives’s Plant (Allium schoenoprasum) came from the wild ancestors that is the native of European and Asian. The ash of chive leaves contain considerable amount of metal, enabling its usage as catalyst in the making of biodiesel. Based on the Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX) characterization, chive leaf ash calcined at 600 ˚C contained 26.14% potassium oxide, 17.55 calcium oxide, 21.94% carbon, and 22.05% phosphorus pentoxide. The ash of chive leaves later on, used as the catalyst on the biodiesel making from the palm oil. The highest biodiesel yield of 94.42% was achieved at reaction temperature of 60 ˚C, 3% catalyst amount, ratio of oil and methanol 1:12, and reaction time 120 minutes. Based on its density, viscosity, moisture, and total glycerol biodiesel has met the Standar Nasional Indonesia (SNI) 7182:2015. However, the purity of biodiesel still haven’t met the standards, in which methyl ester content was 69.13% and the triglyceride was 18.83%.